Astragaloside III Enhances Anti-Tumor Response of NK Cells by Elevating NKG2D and IFN-γ - Chen, Xingmeng; Chen, Xi; Gao, Junxiao; Yang, Han; Duan, Yue; Feng, Yuxin; He, Xin; Gong, Xiaoqun; Wang, Hanjie; Wu, Xiaoli; Chang, Jin (Frontiers in Pharmacology, 2019)
Natural killer (NK) cells play an irreplaceable role in the development of colon cancer, in which antitumor function of NK cells were impaired. Astragaloside III is a natural compound from Astragalus that has been shown to have immunomodulatory effects in various systems. However, few studies have evaluated the antitumor effects of Astragaloside III through stimulating systemic immunity and regulating NK cells. In this study, flow cytometry, immunohistochemical analysis and immunofunctional assays were performed to elucidate the functions of Astragaloside III in restoring antitumor function of NK cells. We demonstrated that Astragaloside III significantly elevated the expression of natural killer group 2D (NKG2D), Fas and IFN-γ production in NK cells, leading to increased tumor-killing ability. Experiments in cell co-culture assays and CT26-bearing mice model further confirmed that Astragaloside III could effectively impede tumor growth by increasing infiltration of NK cells into tumor and upregulating the antitumor response of NK cells. We further revealed that Astragaloside III increased IFN-γ secretion of NK cells by enhancing the expression of transcription factor T-bet. In conclusion, the effective anti-tumor function of Astragaloside III was achieved through up-regulation of the immune response of NK cells and elevation of NKG2D, Fas and IFN-γ production.